2022
DOI: 10.2341/20-066-l
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiotherapy on the Marginal Adaptation of Class II Direct Resin Composite Restorations: A Micro-computed Tomography Analysis

Abstract: SUMMARY This laboratory study was designed to evaluate the marginal adaptation of Class II mesio-occluso-distal (MOD) restorations at the cervical region with micro-computed tomography (micro-CT). Two groups of restorations were compared: 1) those that had been exposed to radiotherapy before restoration was performed using a universal adhesive in etch-and-rinse and self-etch modes; and 2) those that had previously been restored using a universal adhesive in etch-and-rinse and self-etch modes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The three included studies that assessed the marginal adaptation of direct resin-based composite restorations reported conflicting findings. Irradiation did not significantly affect the marginal adaptation of direct resin-based composite restorations bonded with a universal adhesive in one investigation [ 18 ]. In specimens subjected to irradiation before the restorative procedure, more marginal defects were observed in restorations bonded with a universal adhesive applied in self-etch mode compared with the same adhesive in etch-and-rinse mode [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The three included studies that assessed the marginal adaptation of direct resin-based composite restorations reported conflicting findings. Irradiation did not significantly affect the marginal adaptation of direct resin-based composite restorations bonded with a universal adhesive in one investigation [ 18 ]. In specimens subjected to irradiation before the restorative procedure, more marginal defects were observed in restorations bonded with a universal adhesive applied in self-etch mode compared with the same adhesive in etch-and-rinse mode [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation did not significantly affect the marginal adaptation of direct resin-based composite restorations bonded with a universal adhesive in one investigation [ 18 ]. In specimens subjected to irradiation before the restorative procedure, more marginal defects were observed in restorations bonded with a universal adhesive applied in self-etch mode compared with the same adhesive in etch-and-rinse mode [ 18 ]. One study found that the marginal gap of direct resin-based composite restorations was higher in irradiated than unirradiated specimens [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations